Israel yearbook on human rights. (Martinus Nijhoff Publishers, 2006)
The Israel Yearbook on Human Rights - an annual published under the auspices of the Faculty of Law of Tel Aviv University since 1971- is devoted to publishing studies by distinguished scholars in Israel and other countries on human rights in peace and war, with particular emphasis on problems relevant to the State of Israel and the Jewish people. The Yearbook also incorporates documentary materials relating to Israel and the Administered Areas which are not otherwise available in English (including summaries of judicial decisions, compilations of legislative enactments and military proclamations). The highlight of Volume 36 of the Israel Yearbook on Human Rights is a reproduction of the full text and commentary of a new Manual relating to Non-International Armed Conflicts (prepared by a Drafting Committee under the aegis of the San Remo International Institute of Humanitarian Law). This is a sequel to the well-known San Remo Manual on International Law Applicable to Armed Conflicts at Sea, published in 1995. The new Manual reflects the results of a larger Project launched by the Institute, the background papers of which were printed in full in volume 30 (2000) of the Yearbook. The sphere of non-international armed conflicts is gaining increasing importance and attention due to the growing frequency and menace of internal wars. The imperative need to come up with an authoritative restatement of the law governing these conflicts has become obvious. This is a first attempt of its kind, and it is bound to arouse interest and debate.